Hepatitis B virus‐specific T‐cell responses during IFN administration in a small cohort of chronic hepatitis B patients under nucleos(t)ide analogue treatment. Issue 9 (19th November 2013) - Sprinzl, M. F.; Russo, C.; Kittner, J.; Allgayer, S.; Grambihler, A.; Bartsch, B.; Weinmann, A.; Galle, P. R.; Schuchmann, M.; Protzer, U.; Bauer, T.
Summary The effect of pegylated interferon‐α (IFN) add‐on therapy on HBV‐specific T‐cell responses was evaluated in 12 patients with stable, undetectable hepatitis B virus (HBV) load under nucleos(t)ide analogue therapy. Peripheral blood mononuclear cells were isolated at week 0, 4, 8, 12, 24 and 48 of IFN add‐on therapy. Quantity and quality of circulating HBV S‐ and core‐specific CD4 and CD8 T cells were analysed ex vivo by flow cytometry. HBV S‐ and core‐specific CD4 T‐cell numbers modestly increased within 8 weeks of IFN administration (P = 0.0391 and P = 0.0195), whereas HBV‐specific CD8 T cells in general showed only minor changes under IFN add‐on therapy. Functionality of HBV‐specific CD4 but not CD8 T cells positively correlated with serum transaminase activity. In addition, we observed an increase in CD4 T cells producing tumour necrosis factor‐α (TNFα) without antigen restimulation (P = 0.0039), which correlated with elevated transaminases. During IFN add‐on therapy, two patients developed an anti‐HBs seroconversion, only one of whom showed a relevant increase in HBV‐specific T cells. In conclusion, IFN add‐on therapy of chronic hepatitis B increased HBV‐specific T‐cell responses and affected a previously unrecognized TNFα‐monofunctional CD4 T‐cell population. Although the observed T‐cell responses did not correlate with HBsAg seroconversion, we expect additional insights into the immunopathogenesis of hepatitis B, following the characterization of the newly identified TNF α‐monofunctional T‐cell population.